Prenatal Nicotine or Cannabis Exposure and Offspring Neurobehavioral Outcomes. Issue 1 (January 2022) - Smid, Marcela C.; Metz, Torri D.; McMillin, Gwen A.; Mele, Lisa; Casey, Brian M.; Reddy, Uma M.; Wapner, Ronald J.; Thorp, John M.; Saade, George R.; Tita, Alan T. N.; Miller, Emily S.; Rouse, Dwight J.; et al.
Abstract : OBJECTIVE: To study the association between nicotine or cannabis metabolite presence in maternal urine and child neurodevelopmental outcomes. METHODS: We conducted a secondary analysis of two parallel multicenter randomized controlled trials of treatment for hypothyroxinemia or subclinical hypothyroidism among pregnant individuals enrolled at 8–20 weeks of gestation. All maternal–child dyads with a maternal urine sample at enrollment and child neurodevelopmental testing were included (N=1, 197). Exposure was urine samples positive for nicotine (cotinine) or cannabis 11-nor-9-carboxy-delta-9-tetrahydrocannabinol [THC-COOH]) or both metabolites. Primary outcome was child IQ at 60 months. Secondary outcomes included cognitive, motor and language, attention, behavioral and social competency, and differential skills assessments at 12, 24, 36, and 48 months. Quantile regression analysis was performed with confounder adjustment. RESULTS: Of 1, 197 pregnant individuals, 99 (8.3%) had positive cotinine samples and 47 (3.9%) had positive THC-COOH samples; 33 (2.8%) were positive for both. Groups differed in self-reported race and ethnicity, education, marital status, insurance, and thyroid status. Median IQ was similar between cotinine-exposed and -unexposed children (90 vs 95, adjusted difference in medians −2.47, 95% CI −6.22 to 1.29) and THC-COOH-exposed and -unexposed children (89 vs 95, adjusted difference in medians −1.35, 95% CI −7.76 to 5.05). In secondary outcome analysis, children with THC-COOH exposure compared with those unexposed had higher attention scores at 48 months of age (57 vs 49, adjusted difference in medians 6.0, 95% CI 1.11–10.89). CONCLUSIONS: Neither prenatal nicotine nor cannabis exposure was associated with a difference in IQ. Cannabis exposure was associated with worse attention scores in early childhood. Longitudinal studies assessing associations between child neurodevelopmental outcomes and prenatal nicotine and cannabis exposure with a focus on timing and quantity of exposure are needed. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT00388297. Abstract : Neither nicotine nor cannabis exposure in the early prenatal period is associated with difference in child IQ at 5 years of age.